Implication of Climatic Change on Sustainable Environmental and Natural Resource Management: Individual and Collective Responsibility - Okemasisi, Kinikonda (Machakos University Press, 2021)
The impact of climate change is quite evident in terms of increasing aridity, disruption of livelihood in terms of food and drinking water supply, risking the collapse of marine eco-systems, food insecurity, Arctic melting, loss of glaciers, Amazon and Siberian fires, droughts and floods. Several studies in literature support the fact that global warming that causes climate change is due to human activity. This is explained first of all by the use of fossil fuels, and secondly by the balance of emissions from changes in land use. The ocean has absorbed about 30% of human made carbon dioxide emissions which has led to acidification of the waters. Global warming relies mainly on the green-house gas emissions, which are currently increasing. There is need to redesign our curricula and demand that ecology be at the centre of learning at all educational levels as young people need to be taught about the urgency, severity and scientific basis of the climate change crisis. Unless we make a paradigm shift in our curriculum design and development and also change our lifestyles, we risk suffering the worst impact of climatic change. The paper is a review of both theoretical and empirical studies on impact of climate change in Africa and brings to the limelight the global views of this impact in Africa. The paper contributes to new knowledge by suggesting the need for the African nations to collectively take responsibility to address the impact of climate change by recommending a Pan African Ecological Curriculum
Keywords: Impact of climate change; Ecological Curriculum; African Nations; Collective Responsibility